Comparison of the Waspas Method with the OCRA Method in Determining Web-Based Aid Recipients - Randy, Muhammad Randy; Lestari, Silvia (Marqcha Institute, 2025)
The determination of scholarship aid recipients at Pangeran Antasari High School has long relied on a manual and subjective process, leading to inefficiencies, inaccuracies, and potential biases in decision-making. To address this issue, this research aims to develop and compare the effectiveness of two multi-criteria decision-making (MCDM) methods—the Weighted Aggregated Sum Product Assessment (WASPAS) and the Operational Competitiveness Rating Analysis (OCRA)—within a web-based Decision Support System (DSS) for determining scholarship recipients. The study applies both methods using nine evaluation criteria, including socioeconomic and academic factors, to rank eligible students objectively. The results reveal that the WASPAS method produces more consistent, stable, and transparent outcomes, with scores that decline gradually and proportionally across alternatives, while the OCRA method demonstrates higher sensitivity to minor data variations, resulting in less stable rankings. Consequently, WASPAS proves to be more suitable for decision contexts that prioritize fairness, stability, and comprehensive evaluation of multiple criteria. The implementation of this method in an automated DSS enhances the objectivity, efficiency, and accountability of scholarship distribution processes. The study’s findings contribute to the advancement of decision-support frameworks in educational institutions and provide a methodological reference for future applications of MCDM models in resource allocation and policy decision-making.